Juridical Review of the Motor Vehicle Tax Sunset Policy and Impact on Taxpayers - Arum, Fitri Atur (Research Horizon, 2024)
The impact of regional autonomy is very large, one of the impacts of each region from the decentralization policy is the financial condition of the region. Regional fiscal capacity has experienced significant changes. Where previously the local government was very dependent on the central government in terms of financial management. The spirit of decentralization does bring better social change. On the other hand, currently local governments are required to be able to find ways or alternative financing to finance their government expenditures. Sunset Policy on motor vehicle tax is one of the policies to improve local finance. This research has the aim of photographing the Sunset Policy or reduction of motor vehicle tax. The purpose of the provincial government issuing the policy intends that the springs of revenue or tax revenue continue to be hoisted up. This research uses descriptive qualitative methods, data collection is done through observation, interviews and documentation. The conclusion of this research is that the Sunset Policy is quite good in raising funds but there are other things that arise from this policy, namely not fulfilling the principle of justice for taxpayers.